Symbols in political centres. Where they are and what they mean - Herman van der Wusten (Belgeo)
The paper starts from the concept of political centre formation as a necessary and continuing process in the emergence and maintenance of larger differentiated societies. Accommodations of public authorities spatially concentrate within cities, mostly called capitals. The paper is about the ways in which the built environment in which public authorities operate, supports them symbolically. Introductory sections about the use of symbols, signs and icons in this context are followed by sections that take the political centres in the European state system as a relevant example and indicate ways to study this question in a comparative fashion.